2001
DOI: 10.1016/s0969-2126(01)00566-4
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the 100 kDa Arsenite Oxidase from Alcaligenes faecalis in Two Crystal Forms at 1.64 Å and 2.03 Å

Abstract: The large subunit of arsenite oxidase is similar to other members of the dimethylsulfoxide (DMSO) reductase family of molybdenum enzymes, particularly the dissimilatory periplasmic nitrate reductase from Desulfovibrio desulfuricans, but is unique in having no covalent bond between the polypeptide and the Mo atom. The small subunit has no counterpart among known Mo protein structures but is homologous to the Rieske [2Fe-2S] protein domain of the cytochrome bc(1) and cytochrome b(6)f complexes and to the Rieske … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
279
0
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(300 citation statements)
references
References 30 publications
(2 reference statements)
13
279
0
8
Order By: Relevance
“…This enzyme is a heterodimeric protein composed of a small subunit containing a Rieske [2Fe-2S] cluster and a large molybdopterin subunit, harboring a [3Fe-4S] cluster (Ellis et al, 2001). According to the previous studies and unified nomenclature proposed by Lett et al (2012), these subunits are encoded by aioB (small Rieske subunit, previously known as aoxA/aroB/asoB) and aioA (large molybdopyterin subunit, previously known as aoxB/aroA/asoB) genes.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is a heterodimeric protein composed of a small subunit containing a Rieske [2Fe-2S] cluster and a large molybdopterin subunit, harboring a [3Fe-4S] cluster (Ellis et al, 2001). According to the previous studies and unified nomenclature proposed by Lett et al (2012), these subunits are encoded by aioB (small Rieske subunit, previously known as aoxA/aroB/asoB) and aioA (large molybdopyterin subunit, previously known as aoxB/aroA/asoB) genes.…”
Section: Introductionmentioning
confidence: 99%
“…The first crystal structure for a protein of this family was the one reported for DMSOR from Rhodobacter sphaeroides (6). Members of the DMSOR family share the Mo-containing ␣-subunit, such as DMSOR (6)(7)(8), formate dehydrogenase (FDH)-H (9), and dissimilatory nitrate reductase (NIR) (10), but may also have one or two additional small subunits as observed in arsenite oxidase (11) and in tungsten-containing FDH-T (12) (␣-and ␤-subunits), and in NIR A (NARGHI) (13) and FDH-N (14) (␣-, ␤-, and ␥-subunits). The only protein ligand to the Mo ion is either a Ser (DMSOR, TH), Cys (dissimilatory NIR), Asp (NIR A), or seleno-Cys (FDHs).…”
mentioning
confidence: 99%
“…The only protein ligand to the Mo ion is either a Ser (DMSOR, TH), Cys (dissimilatory NIR), Asp (NIR A), or seleno-Cys (FDHs). Arsenite oxidase is unique in having no covalent linkage between the protein and the Mo atom (11). All of these enzymes function as typical Mo hydroxylases, with the Mo ion cycling between Mo(IV) and Mo(VI) during catalytic turnover.…”
mentioning
confidence: 99%
“…The large subunit (AroA~90 kDa) of the arsenite oxidase is the first example of a new subgroup of the dimethylsulfoxide (DMSO) reductase family of molybdoenzymes (Ellis et al, 2001). It is reported that this heterodimeric enzyme is located on the outer surface of the inner membrane, and is transported to the cytoplasmic membrane (Lebrun et al, 2003).…”
Section: As(iii)-oxidizing Bacteriamentioning
confidence: 99%